A cognitive analysis of metaphor in Shona terminological dictionaries. Issue 3 (3rd July 2017) - Mheta, Gift
Abstract: It is well-known among linguists and lexicographers that metaphor plays a pivotal role in the creation of new terminology and its importance in the expansion of the Shona lexicon in response to scientific, technical and educational demands cannot be overemphasised. Like most languages, Shona is growing through the use of lexicon expansion strategies such as borrowing, clipping, derivation and coinage. Through such strategies, lexical gaps that are created in communication are filled, and one linguistic phenomenon that is central in language growth is metaphor. This article is inspired by the fact that lexicographers use metaphor in its varying forms to expand the Shona lexicon, especially in the compilation of terminological dictionaries. The article attempts to contribute towards a broader and deeper understanding of the divergent forms of metaphor and how they are utilised by lexicographers in the compilation of terminological dictionaries. The examples used are drawn from three specialised dictionaries compiled by researchers at the African Languages Research Institute (ALRI) of the University of Zimbabwe, namely, Duramazwi reUrapi neUtano, Duramazwi reMimhanzi and Duramazwi reDudziramutauro noUvaranomwe . The main objective is to show how metaphor is used in language development using tenets of Cognitive Grammar (CG).